Skin Regeneration with a Scaffold of Predefined Shape and Bioactive Peptide Hydrogels - Im, Heejung; Kim, Su Hee; Kim, Soo Hyun; Jung, Youngmee (MARY ANN LIEBERT, INC, 2018)
We developed a highly elastic customized scaffold for soft tissue regeneration and combined them with bioactive hydrogels with stem cell-inducing ability. This was done to mimic mechanical properties of native soft tissues and improve the viability of transplanted cells as well as efficiency of tissue regeneration. The proposed study was aimed at evaluating various characteristics of scaffolds and investigating their tissue-regenerating ability. Finger-shaped porous scaffolds were successfully fabricated by an indirect 3D printing of poly (L-lactide-co--caprolactone) (PLCL), which provides high elasticity for soft tissue engineering. In addition, a self-assembling peptide hydrogel coupled with substance P (RARADADARARADADA/RARADADARARADADA-substance P, RADA16/RADA16-SP) was used to accelerate angiogenesis and recruit intrinsic mesenchymal stem cells (MSCs). This study included three kinds of groups: Group I=PLCL scaffold with human dermal fibroblasts (HDFs) (P+C), Group II=PLCL scaffold with HDFs and RADA16 (P+C+R), and Group III=PLCL scaffold with HDFs, RADA16, and RADA16-SP (P+C+R+S). The samples were implanted into immunodeficient mice subcutaneously and harvested at 1 and 4 weeks. Tissue regeneration was evaluated by histological analysis with hematoxylin and eosin (H&E) and Masson's trichrome (MT) staining. The images showed that a large number of cells were recruited into the scaffolds, and collagen was deposited in the constructs of the P+C+R+S group. Additionally, recruitment of MSCs, angiogenesis, and collagen were observed by immunofluorescence staining. The results show that the P+C+R+S group had more type I and type III collagen, which are formed in soft tissues, and were deposited on the scaffold compared with the other groups. Moreover, more blood vessels and MSCs were induced in the P+C+R+S group than in those of the P+C and P+C+R groups. Consequently, the results suggest that the construct of the customized porous PLCL scaffold and RADA16/RADA16-SP hydrogel could be a good treatment modality to treat skin defects.
Keywords: NEUROPEPTIDE SUBSTANCE-P; MESENCHYMAL STEM-CELLS; ENHANCED ANGIOGENESIS; TISSUE-REPAIR; NANOFIBERS; FABRICATION; RAT; CHITOSAN; COLLAGEN